Is it all too much? - McCrory, P. (British Journal of Sports Medicine, 2007)
I couldn`t help but notice the recent press reports of how the weather was going to be dealt with for the 2008 Beijing Olympics. Having picked the wettest month of the year to hold the Olympic Games, the Chinese have developed one of the world`s largest weather modification strategies. Weather patterns over Beijing in recent decades indicate a 50% chance of rain during the Games. Clearly, this a problem that is in dire need of an Olympic-standard solution.